Intravenous drug abusers presenting with pseudoaneurysm and other surgical complications in Pakistan (Journal of the Pakistan Medical Association, 2020)
Abstract People who inject drugs (PWIDs) reuse injection equipment and other paraphernalia, which is a major source of transmission of human immunodeficiency (HIV) and hepatitis C virus (HCV) infections. PWIDs who use infected injections develop many surgical complications which are life- threatening. The most common complication is infected pseudoaneurysm. To assess complications requiring surgery in drug abusers, a study was conducted in the East Surgical Ward of Mayo Hospital Lahore, Pakistan from Jan 2017 to Jan 2019. A total of 48 PWIDs presented to the surgical department, out of which 39 (81%) were HIV positive, and 31 (64%) were HCV positive. Of the 52% who had pseudoaneurysm, 92% had femoral and popliteal aneurysm and 8% had brachial aneurysm. After ligation and excision of pseudoaneurysm only 8% required major amputation. Mortality rate was 0%. Ligation and excision is a safe option in pseudoaneurysm. Continuous...